(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2024)
Polycystic Ovary Syndrome (PCOS) is a multifaceted endocrine disorder affecting 5-10% of women of reproductive age worldwide. Characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology, PCOS is a leading cause of infertility, metabolic disorders, and psychological distress. The etiology of PCOS remains unclear, but genetic, environmental, and hormonal factors contribute to its pathogenesis. Clinical manifestations include irregular menstrual cycles, hirsutism, acne, and weight gain. Insulin resistance, type 2 diabetes, and cardiovascular disease are common comorbidities. Early diagnosis and management through lifestyle modifications, pharmacological interventions, and surgical options can improve quality of life and reduce long-term health risks.